The flow of transboundary rivers of the Republic of Belarus and Russia in a changing climate - Aksana M. Taurykina; Marina V. Shmakova; Ivan A. Bulak; Anastasiya O. Rusina; Alena I. Hramadskaya (Водное хозяйство России: проблемы, технологии, управление)
Currently, due to the growing anthropogenic load and climate change, studies of the intensity and direction of the dynamics of water resources affecting transboundary watercourses are in demand in order to use and preserve them safely. In this regard, it is relevant to analyze the flow of large transboundary rivers of Belarus and Russia – the Western Dvina and Sozh.